A relevância da Demonstração do Valor Adicionado na evidenciação da distribuição da riqueza: um estudo da DVA na crise de 2008-2009 - Silva, Edilson Muniz da (2010)
The Value Added Statement (VAS) is a statement created with the objective of making known the social responsibility of organizations. In Brazil, it was enacted through Law number 11.638 of December 28, 2007. Thus, VAS started to be part of mandatory financial statements published by publically traded companies, occasion which CVM (the Brazilian equivalent of the American SEC) through CVM act 557 of November 12, 2008, approved the draft of CPC 09 of October 15, 2008, edited into its final form on November 30, 2008, with a model to be utilized by publically traded companies. This study aims to analyze, by use of data gathering of 264 (two hundred and sixty four) publically traded companies VAS s, the final behavior of wealth distribution generated by firms, taking into account the period between 2007 and 2009, that is, prior to the global financial and economic crisis, with the goal of verifying the impact of unstable scenarios and crisis on wealth distribution and generation to such interest groups as employees, government, third-party capital remuneration, and pay equity. The paper tries to analyze and answer if there was an increase or reduction of wealth distribution to the Government during the crisis period and, consequently, if this reduction is gaugeable by use of VAS analysis. To conclude, it tries to verify, among the benefited groups from the wealth distribution of one of the firms, who has lost the most during the crisis period. The methodology used was that of descriptive research. For statistical analyses, the analysis of variance (ONEWAY ANOVA) with significance level less than or equal to 5% (p <0.05), multiple comparison tests in the SPSS system, as well as analysis and percentage of nominal rate for each publically traded companies VAS´s, accumulated according to the Bovespa economic sectors, have been used to test the data. The results show the existence of differences in the value added distribution to public interest, according to various economic sectors. In addition, it was found that the Government's participation in value added - in absolute growth - was constant, and it kept the largest added value share generated in the accumulated DVAS analyzed